Risco de desenvolvimento de transtorno do espectro autista em recém-nascidos pequenos para idade gestacional: Revisão integrativa da literatura - Catarina Marcos Moldã; Sebastião Mota Tavares; Alice Reis Villa-Verde; Élis Mariângela Brito; Ingrid Ribeiro Soares da Mata; Marilucia Rocha de Almeida Picanço (Sociedade Brasileira de Pediatria, 2022)
INTRODUCTION: Autistic Spectrum Disorders (ASDs) are neurodevelopmental disorders characterized by persistent deficits in communication and social interaction, associated with repetitive and restricted patterns of behavior, activities and interests. The etiology of TEAs remains undetermined, being associated with a multifactorial pathogenesis that may be related to genetic factors, alterations during intrauterine brain development and birth, and environmental factors. Within this context, two factors are considered consistent predictors of ASD: birth weight and gestational age. OBJECTIVE: Thus, this study aimed to carry out a literature review to verify if there were reports of a significant relationship between ASD and birth weight and low gestational age. METHODS: A search was carried out between 2010 and 2020 using the following databases: (SciELO, PubMed, PsycINFO, Lilacs, Medline, Google Scholar, BVS and CAPES). RESULTS: 14 articles were selected for full reading and, of these, 35.71% (n=5) with a significant association between low birth weight and ASD. CONCLUSION: The review concluded that the appearance of autism spectrum disorders has a multifactorial influence.